2017
DOI: 10.3389/fonc.2017.00107
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Management of Advanced and Metastatic Renal Cell Carcinoma: A Multidisciplinary Approach

Abstract: The past decade has seen a rapid proliferation in the number and types of systemic therapies available for renal cell carcinoma. However, surgery remains an integral component of the therapeutic armamentarium for advanced and metastatic kidney cancer. Cytoreductive surgery followed by adjuvant cytokine-based immunotherapy (predominantly high-dose interleukin 2) has largely given way to systemic-targeted therapies. Metastasectomy also has a role in carefully selected patients. Additionally, neoadjuvant systemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 163 publications
(166 reference statements)
0
36
0
Order By: Relevance
“…The major type of kidney tumor (80-90%) originates from the epithelial lining of the proximal convoluted tubules and exhibits highly vascularized and metastatic characteristics (2). To date, the primary therapy for localized RCC is surgery (radical nephrectomy and nephron-sparing surgery), while for unresectable and metastatic RCC, the therapeutic options remain limited (3)(4)(5). RCC is sensitive to neither traditional chemotherapy nor radiation therapy (6).…”
Section: Introductionmentioning
confidence: 99%
“…The major type of kidney tumor (80-90%) originates from the epithelial lining of the proximal convoluted tubules and exhibits highly vascularized and metastatic characteristics (2). To date, the primary therapy for localized RCC is surgery (radical nephrectomy and nephron-sparing surgery), while for unresectable and metastatic RCC, the therapeutic options remain limited (3)(4)(5). RCC is sensitive to neither traditional chemotherapy nor radiation therapy (6).…”
Section: Introductionmentioning
confidence: 99%
“…Renal cell cancer (RCC) runs up to 3% of malignant tumors in human beings each year, and surgical resection of these tumors generally results in excellent long-term disease-free survival [1] . However, studies revealed that 20–50% of patients present with locally advanced and distant metastatic disease [2] . Moreover, patients with metastatic RCC (mRCC) of other organs represent an unfavorable subset of individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Zitvogel and colleagues have indicated the immune therapeutic benefits of extracellular vesicles in tumor. They revealed vaccination of mice with extracellular vesicles secreted from dendritic cells (DCs) had functional MHC, T-cell and costimulatory molecules [48] . The DCs were shown to stimulate an antitumor immune response and suppressed tumor growth in a T cell-dependent manner.…”
Section: Extracellular Vesicles and Immunotherapy For Osmentioning
confidence: 99%